Chronic Stress and Its Role in Physiological Aging: Insights from Molecular Biology and Life Sciences - Victoriia Overchuk; Oksana Vdovichenko; Inokentii Korniienko; Tamara Hovorun; Margaryta Kremenchutska; Iryna Kondratieva (The Bioscan, 2024)
Chronic stress is increasingly recognized as a significant factor influencing physiological aging. This article explores the intricate relationship between chronic stress and aging, drawing insights from molecular biology and life sciences. We discuss the biological mechanisms through which chronic stress accelerates aging processes, including oxidative stress, telomere shortening, neuroendocrine dysregulation, and inflammation. A comprehensive literature review highlights existing research on the topic, while the methodology section outlines the approaches used to gather and analyze relevant studies. The results section synthesizes findings from the explored studies, demonstrating the multifaceted impact of chronic stress on aging. The discussion emphasizes the implications of these findings for health and longevity, advocating for stress management as a critical component of healthy aging. Additionally, we investigate translational research insights, emphasizing how findings from zoological studies can inform human health.